FACTORY PHYSICAL ARRANGEMENT PROJECT: a study for setting up a smoked pork factory - de Souza, Fábio Augusto; Bertaci, Moacir José (Revista Interface Tecnológica, 2020)
This article sought to develop a plan for the preparation of physical arrangements to analyze the optimization, through concepts, of a smoked pork products company, located in the city of São José do Rio Preto in the state of São Paulo. Each of the levels of space planning was analyzed, from its strategy at a global level, through the supra, macro and micro levels down to the sub-micro level. The levels were characterized and analyzed considering their relevance for the feasibility analysis of the company in question. Considerations were also made about the types of physical arrangements at each level. All optimization analysis were made aiming at the material flow in the production process and the cost of implanting the factory.